Stop violence against medical workers in China - Yao, Shukun (Pioneer Bioscience Publishing Company, 2014)
The incidence of patient-doctor disputes are alarmingly increasing in China, this article reviews the current status and causes of violence against medical workers in China, six strategies to tackle the daily worrying problems have been proposed and hopefully could improve the medical working environment in China.